Describing Events: Changes in Eye Movements and Language Production Due to Visual and Conceptual Properties of Scenes - Esaulova, Yulia; Penke, Martina; Dolscheid, Sarah (Frontiers in Psychology, 2019)
How can a visual environment shape our utterances? A variety of visual and conceptual factors appear to affect sentence production, such as the visual cueing of patients or agents, their position relative to one another, and their animacy. These factors have previously been studied in isolation, leaving the question about their interplay open. The present study brings them together to examine systematic variations in eye movements, speech initiation and voice selection in descriptions of visual scenes. Forty-four native speakers of German were asked to describe depicted event scenes presented on a computer screen, while both their utterances and eye movements were recorded. Participants were instructed to produce one-sentence descriptions. The pictures depicted scenes with animate agents and either animate or inanimate patients who were situated to the right or to the left of agents. Half of the patients were preceded by a visual cue – a small circle appearing for 60 milliseconds on a blank screen in the place of patients. The results show that scenes with left- rather than right-positioned patients lead to longer speech onset times, a higher probability of passive sentences and looks toward the patient. In addition, scenes with animate patients received more looks and elicited more passive utterances than scenes with inanimate patients. Visual cueing did not produce significant changes in speech, even though there were more looks to cued vs. non-cued referents, demonstrating that cueing only impacted initial scene scanning patterns but not speech. Our findings demonstrate that when examined together rather than separately, visual and conceptual factors of event scenes influence different aspects of behavior. In comparison to cueing that only affected eye movements, patient animacy also acted on the syntactic realization of utterances, whereas patient position in addition altered their onset. In terms of time course, visual influences are rather short-lived, while conceptual factors have long-lasting effects.